Hydroxyapatite and Thermal Oxidation as intermediate Layer on Metallic Biomaterial for medical implant: a review - Arman Shah bin Abdullah (Tanjong Malim, 2019)
Hydroxyapatite and Thermal Oxidation as intermediate Layer on Metallic Biomaterial for medical implant: a review by Arman Shah bin Abdullah